Absorbed doses in bricks and TL-dosimeters due to anthropogenic and natural environmental radiation sources. (January 2021) - Ulanowski, Alexander; Hiller, Mauritius; Woda, Clemens
Abstract: Radiation doses accumulated in ceramic or brick and assessed by thermoluminescence (TL) or optically stimulated luminescence (OSL) measurements are commonly used as a source of independent dosimetric information, helpful for validation of retrospective estimates of population exposures to anthropogenic radiation sources. This work systematically evaluates contributions to the cumulative dose in brick samples located at different heights in a wall from anthropogenic and natural radiation sources and provides data for quantification of the natural background component of the total dose in the brick derived in TL/OSL-measurements. Al- and Cu-cased thermoluminescence dosimeters (TLD) based on Al2 O3 :C are used to measure contemporary doses in brick walls as benchmarks and for validation of the dose reconstruction procedures. Correspondingly, doses in TLD and in brick in the same locations and under the same irradiation conditions are obtained by Monte Carlo simulations of radiation transport in realistic geometries. The data obtained in the simulations indicate that energy response of Al-cased dosimeters agrees better with the energy response of the brick than the response of Cu-cased TLD. The dosimetric data and relationships between doses in TLD and in brick are systematically derived for different locations in the wall and above the ground and used in other dose reconstruction studies with luminescence techniques. Highlights: Dose in brick samples and TLD from anthropogenic and natural radiation sources. Derivation of relationships between energy response and doses in brick and in TLD. Energy response of Al-cased TLD agrees better with brick than Cu-cased TLD. Dose conversion coefficient can be used in dose reconstruction studies.